Interstitial granulomatous dermatitis due to a rare myeloproliferative neoplasia - Sandra Cases-Merida; Ana Lorente-Lavirgen; Amalia Pérez-Gil (Wolters Kluwer Medknow Publications, 2018)
Interstitial granulomatous dermatitis (IGD) was first described in 1993 by Ackerman as a cutaneous reactive disease in patients with arthritis. Since then, numerous cases associated with different hematological and rheumatic disorders have been reported. IGD is a polymorphic entity that usually involves the upper part of the trunk. Histologically, it is defined as a diffuse dermal histiocytic infiltrate of different densities surrounded by fragmented collagen. We report the case of a 56-year-old man with pruritic papules affecting neck, proximal arms and thorax associated with weight loss and chronic fatigue for six months. Two punch biopsies were taken and the specimens showed lymphohistiocytic interstitial infiltrates with fragmented collagen and elastic fibers in dermis. IGD was diagnosed as first manifestation of a rare chronic myeloproliferative hematologic disorder (cMPD) with rearrangement of beta-receptor for platelet-derived growth factor (PDGFRB). After two months of imatinib, lesions regressed completely.